CRIMINAL ELECTIONS AS AN EFFORTS TO EMBRACE PANCASILA DEMOCRACY TOWARDS CONSUMER ELECTIONS IN 2024 - Adi Mansar; Muhammad Arifin (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
The election principle of LUBER, JURDIL as mandated by the 1945 Constitution and TSM as the principle of Pilkada is the foundation of democracy that is free from fraudulent practices and justifies all means for each participant (contestant) and all winning teams registered with the KPU and volunteers. The political contestation of the Regional Head Election by winning one party by cheating by a special election supervisory body (Election Supervisory Body) is an event that is detrimental to democracy, both administrative violations and election crimes. Violations that have occurred since before entering the Pilkada stage until the determination of the winner after the calculation of the results of the vote are actions that must be avoided to maintain and maintain peace, unity. Simultaneous Pilkada Year 2024 held on Wednesday, November 27, 2024 was an agreement between the DPR, KPU, BAWASLU and DKPP which had previously been regulated in Law no. 10 of 2016 concerning Pilkada that there will be simultaneous regional elections in 2024. Problems that arise Can Election Crimes Make the 2024 Elections More Integrity? How can Pancasila Democracy realize the 2024 Pilkada simultaneously as a LUBER ELECTION? In order to realize a clean and authoritative government, it must start from elections with integrity and elections with integrity can be realized, one of which is the strict and fair enforcement of criminal law. Through direct elections, Pancasila democracy can be realized.